(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
The present study was designed to analyse the anatomy of the vegetative and reproductive parts of Turkish Iberis species from a systematic point of view. Samples of leaves, stems, roots, fruits, and seeds of each species were collected, fixed, and processed according to the paraffin method for light microscopy. The numerical analysis derived from 11 anatomical characteristics showed that the number and dimensions of vessels in the root, presence of aerenchyma in the leaf, number and dimensions of palisade parenchyma, and mesophyll type were useful for grouping the Iberis taxa. The testa was composed of four layers: the epidermis, subepidermis, compact tissue, and parenchyma. The testa thickness was a significant character to distinguish the investigated Iberis species. In this study, the traditional classification of Turkish Iberis species was mostly congruent with the dendrogram generated vegetative anatomical properties. Bangladesh J. Plant Taxon. 27(2): 213-224, 2020 (December)